Reliability and smallest worthwhile difference in 1RM tests according to previous resistance training experience in young women - Nascimento, Matheus Amarante do; Ribeiro, Alex Silva; Padilha, Camila de Souza; Silva, Danilo Rodrigues Pereira da; Mayhew, Jerry L.; Filho, Marçal Guerreiro do Amaral Campos; Cyrino, Edilson Serpeloni (Biology of Sport, 2017)
The objective of this study was to determine the familiarization and smallest worthwhile difference (SWD) of one-repetition maximum (1RM) tests in detrained women according to their previous resistance training experience. Three groups of women with varying amounts of previous resistance training experience were recruited: Novice (n = 27, 1 to 6 months), Intermediate (n = 13, from 7 to 12 months), and Advanced (n = 20, 13 to 24 months). All participants performed four 1RM test sessions in the bench press (BP), squat (SQ), and arm curl (AC). A significant (p< 0.05) (group vs. time) interaction was observed in SQ suggesting that more experienced participants needed fewer 1RM test sessions to reach a stable load compared to the less experienced groups. Strength changes (p 0.05), suggesting that experience had no impact on familiarization for these lifts. SWDs suggest that strength gains greater than 2-4% in these lifts would indicate a meaningful improvement in strength beyond random variation from trial to trial no matter the experience of the subject. Women with limited previous resistance training experience do not require more trials to reach load stabilization than those with more experience. Stability of 1RM loads for BP and AC may require only two sessions, while SQ may require at least three trials.